Involvement of Disabled-2 on skin fibrosis in systemic sclerosis. Issue 1 (July 2020) - Mei, Xueqian; Zhao, Han; Huang, Yan; Tang, Yulong; Shi, Xiangguang; Pu, Weilin; Jiang, Shuai; Ma, Yanyun; Zhang, Yuting; Bai, Lu; Tu, Wenzhen; Zhao, Yinhuan; et al.
Highlights: DAB2 expression was enhanced in the skin of SSc patients and DAB2 knockdown ameliorated skin fibrosis induced by BLM. DAB2 knockdown suppressed the number of inflammatory cells and inflammatory gene expression in BLM-induced mouse skin. DAB2 knockdown suppressed the activation of skin fibroblasts. Transcriptome analysis of DAB2 siRNA transfected SSc skin fibroblasts. Abstract: Background: Systemic sclerosis (SSc) is a connective tissue disease characterized by inflammation and fibrosis. Our previous research found Disabled-2 (DAB2) expression was significantly downregulated by salvianolic acid B, a small molecular medicine which attenuated experimental skin fibrosis of SSc. These suggest that DAB2 plays an important role in SSc skin fibrosis, but the role of DAB2 in SSc remains unclear. Objectives: To investigate the role of DAB2 in SSc. Methods: DAB2 expression level was detected in the skin and peripheral blood mononuclear cells of SSc patients. Bleomycin (BLM)-induced SSc mice and primary SSc skin fibroblasts were used to investigate the effect of DAB2 downregulation on fibrosis. RNA-seq transcriptome analysis was performed to underlie the mechanism of DAB2 in fibroblasts. Results: DAB2 expression was enhanced in SSc lesion skin and was positively correlated with fibrotic genes, such as α-SMA and PAI-1. The in vivo study revealed that DAB2 downregulation alleviated skin fibrosis, alleviating skin thickness and reducing collagen deposition, and DAB2 knockdown ameliorated the inflammatory cell infiltration. The in vitro study showed that DAB2 knockdown reduced extracellular matrix genes and proteins expression. Moreover, Transcriptome analysis revealed TGF-β and focal adhesion signaling pathways were the main downregulated pathways involved in DAB2 siRNA treated fibroblasts. Conclusions: Taken together, our results revealed that DAB2 was increased in SSc skin, and DAB2 downregulation inhibited BLM-induced mouse skin fibrosis and SSc skin fibroblasts activation. DAB2 played an important role in the pathogenesis of SSc and DAB2 modulation may represent a potential therapeutic method for SSc.